Development and Validation of the Strengths-Based Nursing and Healthcare Leadership Scale - Frechette, Julie; Boies, Kathleen; Lavoie-Tremblay, Mélanie; Clausen, Christina; Ens Manning, Kimberley; Mastroberardino, Meghan; Lavigne, Geneviève; Gottlieb, Laurie N. (Science of Nursing and Health Practices / Science infirmière et pratiques en santé, 2024)
Introduction: The healthcare system is currently facing significant human resource challenges. Strengths-Based Nursing and Healthcare Leadership (SBNH-L), a unique, value-driven leadership approach, holds great potential in creating healthy workplaces in healthcare.Objective: To develop and validate a scale to measure SBNH-L.Methods: The development and validation of the SBNH-L scale followed a rigorous process including 3 stages: 1) Item generation, 2) Scale development, and 3) Construct validation. For construct validation, a quantitative psychometric design, with two cross-sectional samples, was used (the first sample in February 2021, n = 194 North American healthcare managers and the second sample in April 2022, n = 357 Canadian healthcare workers).Results: The scale showed good psychometric properties (notably, Cronbach’s alphas ranged from .73 to .96) as well as evidence of construct validity; data showed satisfactory fit with the hypothesized 8-factor structure (χ2 = 747.43, df = 224, p<.001), and one-factor long (χ2 = 811.87, df = 252, p <.001) and short versions (χ2 = 97.70, df = 20, p <.001). The scale predicted organizational support (r =.40, p < .01) and work satisfaction of workers (r = .51, p < .01), two key outcomes, beyond other common leadership approaches.Discussion and Conclusion: The SBNH-L Scale is theoretically and structurally strong: the principal component analysis and the confirmatory factorial analyses results aligned with SBNH-L theory and the SBNH-L Scale demonstrated high internal consistency. The scale provides a unique way to tap into the protective potential of SBNH-L and can be used for evaluative and formative purposes of healthcare leaders and their organizations.